Valosin-containing protein is associated with maintenance of meiotic arrest in mouse oocytes†. Issue 4 (21st November 2018) - Peng, Hui; Chen, Jing; Gao, Yuyun; Huo, Jianchao; Wang, Chongchong; Zhang, Yanyan; Xiao, Tianfang
Abstract: Valosin-containing protein (VCP) is a member of the highly conserved AAA (ATPase associated with a variety of cellular activities) superfamily. A previous study has shown that targeted deletion of Vcp in mice results in early embryonic lethality. The aim of the present study was to analyze the expression and localization of VCP and its function in meiotic arrest of mouse oocytes. Vcp mRNA and protein were expressed in multiple mouse tissues. In the ovary, VCP protein was mainly expressed in oocytes and granulosa cells. After ovulation and fertilization, Vcp mRNA and protein were detected in oocytes and preimplantation embryos. Furthermore, VCP protein was localized in both the cytoplasm and nucleus of germinal vesicle (GV)-stage oocytes and preimplantation embryos. Moreover, knockdown of Vcp in GV-stage oocytes led to a significantly increased rate of germinal vesicle breakdown (GVBD). In addition, inhibition of VCP protein improved the GVBD rate in mouse GV-stage oocytes. When VCP inhibition was reversed, the final GVBD rate returned to normal. These results provide the first evidence for a novel function of VCP in meiotic arrest of mouse oocytes. Abstract : A novel function of VCP protein is involved in the control of meiotic arrest in the mouse oocyte.